Relation between innovation and 4.0 industry in micro and small enterprises: Case study research in Durango - Ernesto Geovani Figueroa González; Diana Zoraya Herrera-Reyes; Rosalío Tortolero-Portugal; Felicidad Pérez Saldaña; Jesús Guillermo Sotelo Asef (RAN)
Purpose: To analyze the correlation between the innovation variable and its four dimensions -market-oriented, process, goods or services, and human resources -and Industry 4.0 variable in micro and small enterprises (MYPES) in the municipality of Durango, Mexico.